Strategi Peningkatan Pencapaian Kinerja Guru di Namira Islamic School - Iskandarini; Vivi Gusrini Rahmadani; Rahmat Saleh (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to identify strategies that can be implemented to improve teacher performance at Namira Islamic School, an Islamic-based educational institution in North Sumatra. The study employs a mixed-methods approach, combining both quantitative and qualitative methods to obtain more comprehensive results. The population consists of 104 teachers, with a sample of 51 respondents selected using purposive sampling techniques. Based on a SWOT analysis, Namira Islamic School's strengths include high teacher competence, an inclusive work culture, and solid management support. Development opportunities can be leveraged through partnerships with other institutions and the use of technology. However, weaknesses such as heavy workloads, unequal salary systems, and a lack of comprehensive performance evaluations pose significant challenges. This study recommends strategies to improve performance through more effective workload management, the development of technology-based programs, strategic partnerships, and infrastructure enhancement.